Da creche ao jardim-de-infância: Organização pedagógica e continuidade educativa - Fernandes, Macrina (2015)
We shall present a qualitative study under development in a private urban institution in the north of Portugal, through participant observation, the analysis of non-personal documents issued by the school, interviews to teachers and children, and focus groups with parents. The areas of study are the following: the definition of the organisation and management of the pedagogical work of daycare and kindergarten, the analysis of how formal documents within the school foresee a regulated curriculum alignment, the analysis and understanding of the perspectives of the various agents involved in the effective curriculum alignment, the identification of leniency and constraints as perceived by those involved in the transition process between both educational environments, and finally the identification of the effects of the alignment in educational continuity. The data collected reveals a converging regulated curriculum alignment which, according to those involved in it, takes place in the classroom. The converging organisation and the management of the pedagogical work of daycare and kindergarten enhance the sustainable evolution from one educational level to the next, thus contributing to the development and educational success of the children.